Perspectives on technology readiness, unified theory of acceptance and use of technology, and behavioral intention of online travel agency users - Abdul Aziz, Azdel (2019)
The pace of technology advancement is faster than ever before. The key to success is when the business focuses on online service technology, particularly online travel agencies (OTA) that enables easier and convenient room reservation. However, most of the recent technology acceptance studies have not addressed the consumers’ psychological traits or general belief towards the new adoption of certain systems. In Malaysia, the application of OTA has not been empirically measured to any great extent, where the implementation of this type of reservation system is still in the early stage. It is therefore important to gain an in-depth understanding of the system by examining technology readiness as the psychographic factor and the technology acceptance on customers’ OTA experiences. A survey questionnaire among customers, who have used OTA has been undertaken with a total of 453 respondents where all the data were found usable. The survey was conducted at Malaysia airports. The results from the descriptive analysis revealed that most of the respondents believed technologies can enhance and improve flexibility, efficiency, and control over their daily lives. The outcome also indicated that the respondents were not pioneers in using and owning new technologies. Their main concern is the security of using new technology especially if it involves monetary and personal identity in the transaction. The findings also proved that the Unified Theory of Acceptance and Use of Technology mediates the relationship between Technology Readiness (TR) and Behavioral Intention. The knowledge in this area can benefit the managers in fine-tuning their product positioning as well as communication strategies in order to align the TR profiles of a potential customer based on the different stages involved in the product lifecycle.